Entre memórias e afetos das infâncias: nós fronteiriços na análise na perspectiva dos estudos de gêneros e das sexualidades - Vicentin, Douglas William Oliveira Knop (Universidade Federal de São Carlos, 2023)
We start from the premise that in childhood gender and sexuality norms play a central role in the production of children's subjectivities. The objective of this research was to analyze how childhood affections and resistance are constructed in dissidence of gender and sexuality norms through the narratives and memories of LGBT+ adults who live in the city of Sorocaba. The adopted methodology was thematic oral history. Four interviews were conducted in a hybrid format: online and face-to-face. The prerequisites for choosing the interviewees is that they should be people who recognize themselves and declare themselves on the frontier of gender/LGBT+ sexuality, over 18 years old and peripheral areas. Due to the covid-19 pandemic, we conducted three interviews online via the Google meet app with a maximum time of 120 to 180 minutes and one interview in person for the same amount of time. They are people between 22 and 45 years old, being a heterosexual trans man; A person with no gender designation who associates with men; A cisgender and homosexual man and a heterosexual trans woman. Among the four participants, one declares himself white, another brown and two black collaborators. In the narratives, it was possible to identify multiple strategies and affections invented by these four children in the so-called childhood stage, making it possible to subvert and signify them in a positive way. Each strategy produced by these bodies moved different affections in each experience and encounter, in a complex way and according to each brand, thus being the “us”, intrinsically marked by differences and specificities, even within the designation of the LGBT+ community.
Between childhood memories and affections: border nodes in the analysis from the perspective of gender and sexual studies
Keywords: Afetos; Infância; História Oral; Gênero; Sexualidade; Affections; Infancy; Oral History; Gender; Sexuality; CIENCIAS HUMANAS::CIENCIA POLITICA::COMPORTAMENTO POLITICO